Carbon Trading Literacy in Coastal Communities of Gampong Sungai Lueng-Langsa - Siregar, Mahmul; Tarigan, Vita Cita Emia; Mulyadi, Mahmud; Lubis, Yeti Meliany; Asnawi, M. Iqbal (Mahadi: Indonesia Journal of Law, 2024)
Carbon trading is an activity of buying and selling carbon credits, where the buyer produces carbon emissions that exceed the specified limits. This is regulated in Presidential Regulation (Perpres) Number 98 of 2021 concerning the Implementation of the Economic Value of Carbon to Achieve Nationally Determined Contribution Targets. and Controlling Greenhouse Gas Emissions in National Development. Carbon trading is currently a priority program in the government to reduce greenhouse effect emissions, air conditioning, air pollution and factory waste which result in uncontrolled climate change. Through carbon trading literacy, the public can understand the importance of preserving mangroves in Gampong Sungai Lueng. The use of mangroves is very necessary to control carbon and community economic growth, so from the results of this research the community needs knowledge about carbon trading which is currently included in the government's priority program amidst carbon trading which is currently still an issue that must continue to be socialized to the community. Efforts to preserve mangroves as a marine resource for sustainable development in order to create conditions that are free of emissions from the impact of greenhouses, air conditioning, pollution and waste from factories that pollute the environment which has an impact on society, this is also the case at all times for the environment in all regions in Indonesia.